2019
DOI: 10.3389/fbioe.2019.00120
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in Plant Science: To Make a Long Story Short

Abstract: This mini-review aims at gaining knowledge on basic aspects of plant nanotechnology. While in recent years the enormous progress of nanotechnology in biomedical sciences has revolutionized therapeutic and diagnostic approaches, the comprehension of nanoparticle-plant interactions, including uptake, mobilization and accumulation, is still in its infancy. Deeper studies are needed to establish the impact of nanomaterials (NMs) on plant growth and agro-ecosystems and to develop smart nanotechnology applications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(147 citation statements)
references
References 137 publications
0
144
0
3
Order By: Relevance
“…omics data from tobacco, rice, rocket salad, wheat, and kidney beans, confirmed that metal NM provoke a generalized stress response, with the prevalence of oxidative stress components. [92,93] However, a general view on NM-induced immune responses is difficult, as contradictory results have been obtained by different groups, possibly due to different experimental conditions.…”
Section: Nanomaterials and Activation Of Innate Immune Genes/factorsmentioning
confidence: 99%
“…omics data from tobacco, rice, rocket salad, wheat, and kidney beans, confirmed that metal NM provoke a generalized stress response, with the prevalence of oxidative stress components. [92,93] However, a general view on NM-induced immune responses is difficult, as contradictory results have been obtained by different groups, possibly due to different experimental conditions.…”
Section: Nanomaterials and Activation Of Innate Immune Genes/factorsmentioning
confidence: 99%
“…Silver nanoparticles synthesized from chitin-induced exometabolites from a Trichoderma fusant were able to restrain the phytopathogen Sclerotium rolfsii at a minimum inhibitory concentration (MIC) of 20 µg/ml (Hirpara and Gajera, 2020) by modulating pathogenic gene expression. The effective role of silver nanoparticles in plant disease management in vitro and glass house conditions has been elucidated by some researchers, however, responses of plants toward the particles in fighting diseases remain unknown (Ocsoy et al, 2013;Ilaria et al, 2019).…”
Section: Graphical Abstractmentioning
confidence: 99%
“…In this regard pest management (Brzozowski and Mazourek, 2018), durable molecular breeding (Gheysen and Custers, 2017) are also useful for organic farming. On the other hand, nanobiotechnology has been applied for crop production and precision agriculture (Duhan et al, 2017;Elemike et al, 2019;Sanzari et al, 2019;Shang et al, 2019) and plant disease management (Worralle et al, 2018). During the past two decades various application of biotechnology have provided reliable solutions to the management of several biotic and abiotic factors.…”
Section: Contribution Of Biotech Crops To Sustainable Developmentmentioning
confidence: 99%